2020
DOI: 10.1002/ejic.202000659
|View full text |Cite
|
Sign up to set email alerts
|

Redox Active Hexanuclear Mixed Valence Dicationic Ce(III)/Ce(IV) Coordination Clusters

Abstract: A series of mixed valence hexanuclear dicationic coordination clusters containing two µ4‐O2– bridges with general formula M2+(X–)2 [M = CeIV2CeIII4(µ4‐O)2(L–R)4(val)6(H2O)2; 12+, 32+: R = H, 22+: Me; 12+, 22+: X = CeIII2(val)3(NO3)4, 32+: X = NO3] were synthesized, isolated and characterized. The reaction of cerium(III)nitrate hexahydrate with Schiff base ligand (H2L–R) and o‐vanillin (val‐H) under basic condition led to the formation of M2+(X–)2 and the reaction progress was monitored by mass spectrometric st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Polynuclear lanthanide complexes are of high interest owing to wide possible applications for luminescence sensors (Kreno et al, 2012), thermometers (D'Vries et al, 2013) and markers (Ga ´lico et al, 2021), for magnetic data storage (Xiong et al, 2017) and magnetic refrigeration (Wang et al, 2019;, as secondary building blocks for metal-organic framework (MOF) design (Feng et al, 2020), and as nanoparticles with atomic-precision size control (Russell-Webster et al, 2020) and catalytic properties (Mitchell et al, 2021;Arumugam et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Polynuclear lanthanide complexes are of high interest owing to wide possible applications for luminescence sensors (Kreno et al, 2012), thermometers (D'Vries et al, 2013) and markers (Ga ´lico et al, 2021), for magnetic data storage (Xiong et al, 2017) and magnetic refrigeration (Wang et al, 2019;, as secondary building blocks for metal-organic framework (MOF) design (Feng et al, 2020), and as nanoparticles with atomic-precision size control (Russell-Webster et al, 2020) and catalytic properties (Mitchell et al, 2021;Arumugam et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For Ce 4+ , the peaks at 882.2, 888.5, and 898.4 eV belong to 3d 5/2 while peaks at 900.8, 907, and 916.6 eV belong to 3d 3/2 . It has been found that Ce 3+ coordinated by nitrogen donor ligands can spontaneously undergo oxidation to produce Ce 4+ under aerobic conditions . Since CetpyCN is stored in an aerobic environment after synthesis, it is assumed that the presence of Ce 4+ is due to the partial oxidation of Ce 3+ to Ce 4+ .…”
Section: Results and Discussionmentioning
confidence: 98%
“…44 It has been found that Ce 3+ coordinated by nitrogen donor ligands can spontaneously undergo oxidation to produce Ce 4+ under aerobic conditions. 45 Since CetpyCN is stored in an aerobic environment after synthesis, it is assumed that the presence of Ce 4+ is due to the partial oxidation of Ce 3+ to Ce 4+ . Due to the introduction of terpyridine−lanthanide complexes, the fractions of elements and functional groups of LutpyCN and CetpyCN differ from those of CN (Tables S1−S3).…”
Section: ■ Introductionmentioning
confidence: 99%
“…[15] However, unlike acetophenones or benzophenones analogs, [16] salicylaldehyde derivatives display reduced chelating ability toward metal or metalloid ions, unless an additional chelating group is inserted in the vincinity. [17] Nevertheless, some coordination complexes involving salicylaldehyde derivatives have been described. [18] Salicylaldehydes derivatives typically display weak emission in solution due to the possibility of Excited-State Intramolecular Proton Transfer (ESIPT) emission, owing to the presence of 6-membered H-bonded ring.…”
Section: Introductionmentioning
confidence: 99%